Pro T-SQL Programmer's Guide - Natarajan, Jay; Bruchez, Rudi; Coles, Michael; Shaw, Scott; Cebollero, Miguel (Apress : Imprint: Apress, 2015)
Pro T-SQL Programmer's Guide is your guide to making the best use of the powerful, Transact-SQL programming language that is built into Microsoft SQL Server's database engine. This edition is updated to cover the new, in-memory features that are part of SQL Server 2014. Discussing new and existing features, the book takes you on an expert guided tour of Transact-SQL functionality. Fully functioning examples and downloadable source code bring technically accurate and engaging treatment of Transact-SQL into your own hands. Step-by-step explanations ensure clarity, and an advocacy of best-practices will steer you down the road to success. Transact-SQL is the language developers and DBAs use to interact with SQL Server. It's used for everything from querying data, to writing stored procedures, to managing the database. Support for in-memory stored procedures running queries against in-memory tables is new in the language and gets coverage in this edition. Also covered are must-know features such as window functions and data paging that help in writing fast-performing database queries. Developers and DBAs alike can benefit from the expressive power of T-SQL, and Pro T-SQL Programmer's Guide is your roadmap to success in applying this increasingly important database language to everyday business and technical tasks. Covers the newly-introduced, in-memory database features Shares the best practices used by experienced professionals Goes deeply into the subject matter − an advanced book for the serious reader.